Anesthetic Management for a Patient with Kidney Tumor with Inferior Vena Cava Thrombus Utilizing Cardio-Pulmonary Bypass: A Case Report - Mazen S. Faden, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Primitive neuroectodermal tumors are very rare in adults or children, and rarely affect the genitourinary system and usually are large tumors on presentation. These tumors are highly aggressive and can metastasize to lung, pleura, bones and liver. The present case is a 15-year-old female, who was presented with a huge renal mass with tumor extending into the inferior vena cava. She underwent complete removal of the primary kidney tumor, and removal of the IVC tumor utilizing cardio-pulmonary bypass and deep hypothermic circulatory arrest.